Designing an Interactive Game to Encourage Cognitive Empathy as a Bullying Prevention Tool - Baharin, Hanif; Sanim Mohd Fauzi, Shukor; Ahmad, Azlina; Mohmad Kamal, Fazillah (International Journal of Engineering and Technology, 2018)
Bullying can have detrimental consequences to the victims, hence there is a need for bullying prevention programs at school. In this paper, we describe a gameplay model which may be usedto elicit cognitive empathy as a part of anti-bullying program among schoolchildren. We interviewed 79 schoolchildren from four schools in order to find out their understanding of bullying and their play behavior, and we observed their play behaviorduring recess. We found that most schoolchildren in our study instinctively know that bullying is wrong because it hurt others but attributethe consequences to self as imposed by authorities as the reason why hurting others is wrong. We argue that, this shows that they demonstrate affective empathy but would benefit from cognitive empathy training. From our findings we came out with design guidelines and produced a bullying morality conceptual model, which then informed our gameplay model. To validate the gameplay model, we designed and tested an indoor physical computing game prototype that encourages player to collectively exercise their cognitive empathy. The results from our game testing shows that the game mechanics proposed in our gameplay model do encourage players to exercise the empathy.
Keywords: Game design; bullying; schoolchildren; empathy.